The impact of financial reporting of earnings per share on the quality of financial reporting - ابراهيم لبنى زيد; ابراهيم مروة رعد (Journal of Economics and Administrative Sciences, 2016)
This research deals with the case of the Iraqi joint-stock companies listed on the Iraq Stock Exchange study in terms of compliance with the requirements of IAS 33 "Earnings per share" and the research problem Alrtash concentrated in a statement the commitment of those companies the requirements of the International Standard 33, which may adversely affect the quality of financial reporting where and in particular the quality of accounting information and content of the primary and secondary characteristics make them be of interest to the decisions of its users, so the aim of this research to the statement of financial reporting earnings per share on the quality of financial reporting in listed shareholding in Iraq Stock Exchange companies effect, have shown results Find that those companies do not disclose earnings per share only two out of sixteen companies, which represent the research sample in addition to not Obligate the requirements of International Accounting Standard 33 "Earnings per share", and based upon suggested researchers apply the international standard 33 through the introduction of base Iraqi accounting be similar to the international standard, including 33 Iraqi companies listed in Iraq Stock Exchange companies do not apply international standards, or that is the introduction of a clause in both rules Mahspitan sixth and tenth and the newly created item within the scope of IAS 33 .